KONSERVASI ENERGI PANAS SISA PROSES GEOTHERMAL POWER PLANT - Harun Al Rosyid; Hani D. Putra (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2020)
AbstractCurrent technology advances situation is in line with electrical energy demand, but this is not in line with theavailability of resources that produce electrical energy, in order to that it requires energy conservation to increaseefficiency and optimization of a power plant so it can support increasing of electricity demand. This paper gives afeasibility analysis of heat energy conservation from geothermal power plant waste heat as the main power plant.By using the Organic Rankine Cycle (ORC) System with Iso-Butene as a working fluid, by calculating the heatbalance of the ORC cycle, until getting the enthalpy and entropy value of the system, thus we can be calculating theenergy can produce by the expansion turbine which drives the generator, with the result of this research is theadditional energy produce by the ORC system. Taking into account safety, health (SHE) and environmental aspectsas well as turbine design aspects, Iso-Butene was selected as a working fluid with a medium exit area value, whichaffects the size of the turbine and SHE aspects. Low Toxic Level, Zero ODP Value, GDP, GWP value 3.Keywords: ORC, Enthalpy, Entropy, Efficiency, Cycle